Refining professional knowing as a creative practice: towards a framework for Self-Reflective Shapes and a novel approach to reflection. Issue 1 (2nd January 2020) - Kirkman, Philip; Brownhill, Simon
ABSTRACT: This paper introduces a theoretical framework for the Self-Reflective Shapes approach, a creative solution that was developed in response to a practical challenge of supporting the development of a culture of reflection. We frame the problem empirically by outlining the context of our work with Kazakhstani teacher-trainers and theoretically by examining conceptions of professional knowing and reflection that can lead to the overemphasis of either explicit, well-defined knowledge outcomes or tacit, ill-defined embodied knowledge. Drawing on diverse reflective traditions, in this context reflection is focused on developing the freedoms necessary to successfully meet competing educational demands, be they academic, standards-based, developmental, or social-transformational in nature. We propose that acts which balance freedoms and constraints are inherently creative and therefore reflection can be seen as a creative act. This in turn offers a vehicle to manage tensions that arise from the divergent pressures which arise across educators' experiences. Self-Reflective Shapes is presented as an example of such a creative approach as it empowers teachers to focus on the tensions and intentions that are of greatest concern in their context as well as addressing the need to simultaneously develop diverse knowledge forms when addressing multiple, ill-defined and competing educational problems.